Performance analysis of 2.4 GHz ISM-Band wireless LAN for indoor wireless communication links - Ngajikin, Nor Hafizah (Penerbit UTM, 2007)
Wireless communication is one of the fastest growing segments of the telecommunication and consumer electronics industries. The powerful technology and market trends towards portable computing and communications imply an increasingly important role for wireless access in the next generation. However, there are several obstacles that will deduce the network performance such as architectural design of building, placement and composition of wall, furniture arrangement and any other factors. Thereby, this chapter presents a propagation measurement analysis for indoor wireless communication performance. Measurement is done by using Network Stumbler and IxChariot software at operating frequency of 2.4 GHz based on IEEE 802.11b standard. The indoor radio wave propagation in U-shape building was predicted within 2nd floor, block UA2, Kolej 9, Universiti Teknologi Malaysia (UTM). 13 Access Point (AP) are arranged to setup the whole network. Network performances are analyzed based on response time, transaction rate, connectivity, delay and throughput in the network. Comparison of different file size and distance between AP to study the behavior of the network is presented.